48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-114
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Shock-Turbulence Interactions Using High-Order Shock-Fitting Algorithms

Abstract: High-order methods are critical for reliable numerical simulation of strong-shock and turbulence interaction problems. Such problems are not well understood due to limitations of numerical methods. Most widely used shock capturing methods for the numerical simulation of compressible flows are inherently dissipative, only first order accurate and may incur numerical oscillations near the shock waves. In our previous work [1, 2] we have shown that algorithms based on shock-fitting methodology can solve the flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…We have shown that the shock-fitting implementations that are uniformly high order accurate [30][31][32][33] and suffer no spurious oscillations around the shock as generally observed with shock capturing formulations. We have implemented these shock-fitting methods for shock and isotropic turbulence interaction problems.…”
Section: Achievementsmentioning
confidence: 54%
See 2 more Smart Citations
“…We have shown that the shock-fitting implementations that are uniformly high order accurate [30][31][32][33] and suffer no spurious oscillations around the shock as generally observed with shock capturing formulations. We have implemented these shock-fitting methods for shock and isotropic turbulence interaction problems.…”
Section: Achievementsmentioning
confidence: 54%
“…7 for inflow conditions of case II. Some results for inflow of case I were presented in our previous study [30]. It is observed that the jump in the mean turbulent density and pressure is smaller than that observed in the laminar flow.…”
Section: Mean Profilesmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, spurious numerical oscillations have been observed when solving strong-shock and turbulence interaction problems with shock-capturing schemes [7,8]. In our previous work [6,9,10], we presented shock-fitting algorithms that converge with high-order accuracy near as well as away from the shock. These methods were also extended for direct numerical simulation of shock-turbulence interactions [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [6,9,10], we presented shock-fitting algorithms that converge with high-order accuracy near as well as away from the shock. These methods were also extended for direct numerical simulation of shock-turbulence interactions [10]. In this paper, we present extensive results to estimate effects of mean Mach number, turbulent Mach number and Reynolds number on post-shock flow in shock-turbulence interactions.…”
Section: Introductionmentioning
confidence: 99%